German dairy farmers’ implementation of veterinary recommendations to improve calf health—a qualitative study based on the transtheoretical model - Douay--Ryckelynck, Marieke; Retzler, Patricia; Meier, Kim K.; Merle, Roswitha; Stock, Annegret; Jensen, Katharina Charlotte (Frontiers in Veterinary Science, 2025)
IntroductionCalf health is still giving cause for concern, even though best management practices have been known for a long time. This qualitative study aimed to gain insights into the adoption of veterinary recommendations by farmers of large dairy herds to improve the health of calves in Saxony, Germany.MethodsIn the first year of study, nine large dairy farms were visited twice to assess data on calves’ health after assessing the perception of farmers regarding major calves’ diseases. Then, farmers and study veterinarians discussed the results and agreed on three to five measures per farm. Stages of change according to the transtheoretical model, as well as barriers and motivators, were assessed for the following year.ResultsThe perception of farmers and the prevalence assessed by study veterinarians correlated moderately. However, the farmers assessed calves’ health better than the comparison with reference data indicated. In total, farmers implemented 15 of 36 recommendations within 1 year (42%). Barriers hindering the implementation were related to concerns that the team would or could not comply, the belief in the effectiveness of measures as well as the old buildings. Recommendations that needed constant changes in management were less likely to be implemented. Especially offering roughage and water to the calves—a measure mostly suggested by the study team—were seldom implemented or were given up before the study ended. However, factors mentioned positively were necessity and simplicity of recommendations.DiscussionThis study indicates that farmers are, in general, willing to adopt measures to improve the health of calves. However, staff shortage and the motivation of team members played a crucial role in these large dairy farms. Moreover, constant feedback and evaluation of success are needed to encourage farmers to maintain those measures that need constant action.